RUMOURS AND INFODEMICS: JOURNALIST'S SOCIAL MEDIA VERIFICATION PRACTICES DURING THE COVID-19 PANDEMIC - Chelin Indra Sushmita; Pawito Pawito; Andre Noevi Rahmanto (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
Abstract. The spread of rumors and infodemics on the Internet and social media during the Covid-19 pandemic which is unstoppable and usually believed to be the truth is more dangerous than the transmission of the Covid-19 outbreak because it has the potential to threaten safety, cause racism, and hatred of the community. It is the duty of journalists to doing fact-checking and corrects any rumors or infodemics. Fact-checking is one of the most important elements of professional journalism. Technological advances have made infodemics spread rapidly which has become a new challenge for professional journalists as information agents and spearheads of accurate reporting. This became the basis for mass media companies such as Kompas.com and Solopos.com to form journalism team checks to verify the facts and infodemics rumors that circulated widely on the Internet and social media during the Covid-19 pandemic. Fact-checking journalism is a new trend in digital journalism studies. This paper reviews the work practices of fact-checking journalists in verifying infodemics from social media content as the spearhead of accurate reporting as well as a manifestation of hypermedia organizations. A series of qualitative interviews were conducted with journalists at Solopos.com and Kompas.com who were in charge of the fact-check section. The results showed that journalists carried out a series of processes both manually and utilizing digital technology in verifying content and checking several facts to ensure rumors and infodemics on social media about Covid-19 that were spread on social media be compiled into news using journalistic principles. The work process of fact-checking journalists is often done collaboratively to form hypermedia organizations.Keywords: rumors, infodemics, online journalism, fact-check, covid-19, journalism, journalists Abstrak. Persebaran rumor dan infodemik di Internet dan media sosial selama pandemi Covid-19 yang tidak terbendung dan sering kali diyakini sebagai kebenaran oleh masyarakat dinilai jauh lebih berbahaya daripada penularan wabah Covid-19, karena berpotensi mengancam keselamatan, menimbulkan rasisme, serta kebencian terhadap suatu golongan. Sudah menjadi tugas jurnalis dan untuk mengecek fakta dan meluruskan setiap rumor serta infodemik yang beredar di masyarakat. Pengecekan fakta adalah salah satu elemen penting dalam jurnalisme profesional. Kemajuan teknologi membuat infodemik tersebar dengan cepat yang kemudian menjadi tantangan baru bagi jurnalis profesional sebagai agen informasi dan ujung tombak pemberitaan yang akurat. Hal ini menjadi landasan bagi perusahaan media massa berskala nasional seperti Kompas.com maupun lokal, yaitu Solopos.com membentuk tim jurnalisme cek fakta untuk memverifikasi rumor serta infodemik yang beredar luas di internet dan media sosial. Jurnalisme cek fakta merupakan tren baru dalam perkembangan jurnalisme digital. Tulisan ini mengulas praktik kerja jurnalis pemeriksa fakta dalam memverifikasi infodemik dari konten media sosial sebagai ujung tombak pemberitaan yang akurat sekaligus sebagai manifestasi organisasi organisasi hipermedia. Serangkaian wawancara kualitatif dilakukan kepada jurnalis di Solopos.com dan Kompas.com yang bertugas sebagai jurnalis pemeriksa fakta. Hasil penelitian menunjukkan para jurnalis melakukan serangkaian proses verifikasi konten dan pengecekan fakta baik secara manual maupun memanfaatkan teknologi digital untuk mengkonfirmasi rumor serta infodemik tentang Covid-19 yang tersebar di media sosial untuk disusun dalam berita sesuai kaidah jurnalistik. Proses kerja jurnalis pemeriksa fakta ini sering kali dilakukan secara kolaboratif yang membentuk organisasi hipermedia.Kata kunci: rumor, infodemik, jurnalisme online, cek fakta, covid-19, jurnalisme, jurnalis